2023
DOI: 10.3389/fped.2023.1211306
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of lung and diaphragm ultrasound in predicting infant weaning outcomes: a systematic review and meta-analysis

Yang Gao,
Hong Yin,
Mei-Huan Wang
et al.

Abstract: BackgroundAlthough lung and diaphragm ultrasound are valuable tools for predicting weaning results in adults with MV, their relevance in children is debatable. The goal of this meta-analysis was to determine the predictive value of lung and diaphragm ultrasound in newborn weaning outcomes.MethodsFor eligible studies, the databases MEDLINE, Web of Science, Cochrane Library, PubMed, and Embase were thoroughly searched. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS−2) method was used to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In a recently published meta‐analysis evaluating the rule of lung and diaphragm ultrasound in predicting successful weaning in infants, the authors concluded that low DE and low DTF had high sensitivity and moderate specificity in predicting extubation failure and that DTF was more accurate than DE 29 . However, the included studies enrolled neonates, infants and even children which may affect the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published meta‐analysis evaluating the rule of lung and diaphragm ultrasound in predicting successful weaning in infants, the authors concluded that low DE and low DTF had high sensitivity and moderate specificity in predicting extubation failure and that DTF was more accurate than DE 29 . However, the included studies enrolled neonates, infants and even children which may affect the accuracy of the results.…”
Section: Discussionmentioning
confidence: 99%